2011
DOI: 10.1007/s00542-011-1355-2
|View full text |Cite
|
Sign up to set email alerts
|

Innovative design of hollow polymeric microneedles for transdermal drug delivery

Abstract: Hypodermic injections give the best results in terms of drug administration efficiency,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…To date, there are contradictory opinions as to whether DMN will need to be used in combination with an applicator device. Several researchers and companies have reported the development of applicators for MN patches and the topic has been reviewed elsewhere 102105. In the case of DMN, numerous studies have clearly demonstrated that DMN can be easily and reliably inserted into the skin by minimally trained personnel and patients, but further in-depth studies are required to ascertain if variability exists between users.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To date, there are contradictory opinions as to whether DMN will need to be used in combination with an applicator device. Several researchers and companies have reported the development of applicators for MN patches and the topic has been reviewed elsewhere 102105. In the case of DMN, numerous studies have clearly demonstrated that DMN can be easily and reliably inserted into the skin by minimally trained personnel and patients, but further in-depth studies are required to ascertain if variability exists between users.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Our laboratory developed hollow polymer microneedles, which are 900 m microns tall structures in a 4 by 4 arrays, with a pitch to pitch distance of 2 mm. Detailed description of manufacturing and mechanical properties can be found in Sausse Lhernould and Delchambre (2011). Davis et al (2004) measured the insertion force for metal microneedles with a tip radius between 30 and 80 m and found results varying between 0.08 N and 3.04 N. Using needles with a tip diameter between 55 and 115 m, Park et al (2006) report forces between 0.8 N and 1.29 N. Recently developed ultrasharp microneedles (Roxhed et al, 2007), with 0.1 m tip radius, show the ability to insert into skin with a force less than 10 mN.…”
Section: Q2mentioning
confidence: 99%
“…Chen et al (2008) also outlined a fabrication process which used silicon oxide layers on silicon followed by a positive photoresist treatment for pattern transfer onto the silicon oxide layer via RIE and finally producing microneedle tips using an isotropic RIE process. Lhernould and Delchambre (2011) arrived at a design fabrication process of implementing laser ablation to create microchannels in polycarbonate material. Matteucci et al (2009) adapted the micro-fabrication process known in German as lithographie, galvanoformung, abformung (lithography, electroplating and molding) by Hruby (2001) which produced microneedles by double-exposure, deep X-ray lithography (Kim et al 2004) using microcrystalline silicon wafers surfaced with Cr/Au bilayer as a template.…”
Section: Preparation Of Biodegradable Microneedlesmentioning
confidence: 99%
“…Conventional hypodermic needle delivery causes pain and anxiety, and requires medical personnel for administration. In contrast, the biodegradable microneedle, a drugloaded vehicle moulded into an all-in-one drug formulated micro-structure constructed from either biopolymer or sugar excipients, can be used to deliver drug almost painlessly to humans (e.g., Donnelly et al 2010;Lhernould and Delchambre 2011;Olatunji and Das 2011;Gittard et al 2012). These microneedles are economical due to fairly cheap materials, reproducible and are generally safe if microneedle fragments break off after piercing the skin surface as compared to other microneedles made with glass or metal.…”
Section: Introductionmentioning
confidence: 99%